Implementasi Peraturan Presiden Nomor 75 Tahun 2017 Tentang Penilaian Kembali Barang Milik Negara/ Daerah (Studi Kasus Pencatatan Aset Tanah Pada Badan Pengelola Keuangan Dan Aset Daerah Kabupaten Sekadau) - Petty Ansari; Yulius Yohanes; Arifin Arifin (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study aims to examine the implementation of Presidential Regulation Number 75 of 2017 concerning the Revaluation of State/Regional Assets (BMN/BMD) in Sekadau Regency, focusing on land asset recording by the Regional Financial and Asset Management Agency (BPKAD). The research employs a qualitative approach with descriptive methods to describe the policy implementation process and identify the factors influencing its success. Data was collected through in-depth interviews with key informants, including BPKAD officials and related agencies, and secondary data from policy documents, reports, and official data on the SIPD implementation. The findings indicate that the implementation of the SIPD in Sekadau Regency has not been optimal due to challenges such as limited information technology infrastructure, a lack of trained human resources, poor coordination among government units, and insufficient political support. Additionally, resistance to change and conventional work habits hinder the comprehensive application of the SIPD. To address these challenges, it is necessary to enhance human resource capacity, strengthen technology infrastructure, improve inter-organizational communication, and secure stronger political support.This research contributes to the development of public administration knowledge and offers practical recommendations for local governments to improve their SIPD implementation strategies. The implications highlight the importance of a comprehensive approach and effective coordination among stakeholders to achieve better governance.